ANALIS PENDAPATAN USAHA PETERNAKAN SAPI RAKYAT DI KECAMATAN BESITANG KABUPATEN LANGKAT - Ahmad Fauji Lubi; Adhona Bhajana Wijaya Negara; Alfath Rusdhi (Journal of Innovation Research and Knowledge, 2025)
This research aims to determine the income of people's cattle farming businesses in Besitang District, Langkat Regency. implemented in Besitang District, Langkat Regency, North Sumatra Province. The research method used is direct observation, the data collected is primary and secondary data. Characteristics of breeders are the age of productive breeders, namely 40-50 years, 46 people (57.50%), the education level of the breeders, most of them have junior high school education, 35 people (43.75%) and farming experience, namely 11-20 years, 49 people (62.03%). Analysis of sheep farming businesses in Besitang District, Langkat Regency, North Sumatra Province, with an average profit and loss value of IDR 8,060,632 and a B/C value of 1.8. This shows that raising cattle is economically feasible